2010
DOI: 10.1007/s11250-010-9757-1
|View full text |Cite
|
Sign up to set email alerts
|

Virulence repertoire of Shiga toxin-producing Escherichia coli (STEC) and enterotoxigenic Escherichia coli (ETEC) from diarrhoeic lambs of Arunachal Pradesh, India

Abstract: A total of 107 faecal samples were collected from diarrhoeic lambs of high altitude terrains (2,000 to 5,000 m above the mean sea level) of Tawang and West Kameng districts of Arunachal Pradesh, India. Total 234 Escherichia coli were isolated and further subjected to PCR for the study of virulence repertoire characteristics of Shiga toxin-producing E. coli (STEC) and enterotoxigenic E. coli (ETEC). Out of the 234 isolated E. coli, 32% were found positive for STEC, and 9% were carrying virulence gene for ETEC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 28 publications
1
18
1
1
Order By: Relevance
“…In our study, the stx2 gene was more prevalent than the stx1 gene. This result contrasts with reports which showed that STEC strains isolated from small ruminants harbour the stx1 gene more frequently (B h a t et al 2008; Wa n i et al 2009) but agrees with Bandyopadhyay et al (2011), who also found a predominance of the stx2 gene in STEC strains isolated from small ruminant with diarrhoea in India. Jenkins et al (2002) reported that among healthy cattle, prevalence of VTEC strains may vary depending on the season.…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…In our study, the stx2 gene was more prevalent than the stx1 gene. This result contrasts with reports which showed that STEC strains isolated from small ruminants harbour the stx1 gene more frequently (B h a t et al 2008; Wa n i et al 2009) but agrees with Bandyopadhyay et al (2011), who also found a predominance of the stx2 gene in STEC strains isolated from small ruminant with diarrhoea in India. Jenkins et al (2002) reported that among healthy cattle, prevalence of VTEC strains may vary depending on the season.…”
Section: Resultscontrasting
confidence: 91%
“…in small ruminants from Turkey (Gokce et al 2010) and other states (Wani et al 2004), however, research on classification of enterovirulent E. coli and its virulence genes is limited. Recent studies have reported (Wani et al 2003;Bhat et al 2008;Bandyopadhyay et al 2011), the existence of at least one virulence gene in 41%, 36.7%, and 32.6% of E. coli isolates, respectively. In our study we found at least one virulence gene for EHEC or STEC, EPEC, ETEC, EIEC, and EAEC among 36.4% of the isolates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental contaminations and poor herd and milking managements are important causes of reduction of milk quality. The high frequency of stx2 in faecal samples collected from buffalo, cows, and goats described elsewhere (Islam et al, 2008;Stephan et al, 2008;Bandyopadhyay et al, 2011Bandyopadhyay et al, , 2012 might explain the prevalence of stx2 positive STEC in raw milk. In humans, epidemiologic data suggest that E. coli O157 strains that express stx2 are more important than stx1 in the development of HUS, and that strains that express stx2 alone are more likely to be associated with the progression to HUS than strains that produce both stx1 and stx2 (Griffin, 1995) In this study, the presence of STEC harboring the genes stx1 and stx2 in raw milk sample was detected.…”
Section: Preparation Of Template Dnamentioning
confidence: 77%